Effects of a brief mindfulness-based intervention program for stress management among medical students: the Mindful-Gym randomized controlled study - Phang, Cheng Kar (Springer Nature B.V., 2015)
Pursuing undergraduate medical training can be very stressful and academically challenging experience. A 5-week mindfulness-based stress management (MBSM/Mindful-Gym) program was developed to help medical students cope with stress. The aim of this study was to evaluate the effectiveness of the intervention in reducing stress among students in a medical school in Malaysia. Seventy-five medical students participated in the program. They were stratified according to years of studies and randomly allocated to intervention (N = 37) and control groups (N = 38). The following outcome variables were measured at pre- and post-intervention: mindfulness (with Mindful Awareness Attention Scale); perceived stress (with Perceived Stress Scale); mental distress (with General Health Questionnaire), and self-efficacy (with General Self-efficacy Scale). Hierarchical multiple regressions were used to analyse the effect of group (intervention vs. control) on changes in the outcome variables. There were significant improvements at one week post-intervention in all outcome variables: mindfulness (β = 0.19, ΔR2 = 0.04, p = .040, f 2 = 0.05), perceived stress (β = −0.26, ΔR2 = 0.07, p = .009, f 2 = 0.10); mental distress (β = −0.28, ΔR2 = 0.10, p = .003, f 2 = 0.15); and self-efficacy (β = 0.30, ΔR2 = 0.09, p < .001, f 2 = 0.21). Six months after the intervention, those who had joined the program reported higher self-efficacy compared to those in the control group (β = 0.24, ΔR2 = 0.06, p = .020, f 2 = 0.08); but there was no difference in other outcome measures. More than 90 % of the participants found the program applicable in helping patients and all reported that they would recommend it to others. This study indicates that the program is potentially an effective stress management program for medical students in Malaysia.